THE MEANING OF THE DOCTRINE “THE THEORIST OF THE NAQSHBANDIYA SECT” IN THE EDUCATION OF THE YOUTH OF THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In this article, Khoja Muhammad Porso's thoughts on the sacred words used in the Khojagan-Naqshbandiya order are analyzed philosophically. The noble goals of encouraging man to protect himself from himself and to be compassionate by forming a high respect for his species are highlighted.